A new species of Salvia from the Fulgentes clade (Lamiaceae), from Puebla, Mexico - Martínez-Ambriz, Emmanuel; Fragoso-Martínez, Itzi; Martínez-Gordillo, Martha (Phytotaxa, 2019)
A new species of Salvia from the state of Puebla, Mexico, is described and illustrated: Salvia gavilanensis sp. nov., growing in oak forests and oak scrubs, located in the Biosphere Reserve of Tehuacán-Cuicatlán. The new taxon is morphologically similar to S. microphylla, but differs by the herbaceous habit (vs. suffrutescent or shrubby), the strigulose pubescence of the leaves (vs. puberulent to tomentulous), bracts with the margin irregularly denticulate and persistent until the beginning of the anthesis (vs. bracts with the margin entire and deciduous before the anthesis), papillae inside the corolla tube with bidentate apex (vs. papillae with trilobate apex), and the lower lip of the corolla shorter in length compared to the upper lip (vs. lower lip of the corolla longer than the upper lip). Additionally, a phylogenetic analysis based on molecular data (nuclear ITS and the plastid regions trnL-trnF and trnH-psbA) was conducted to explore the relationships of the new species. According to the results, the new species belongs to the Fulgentes clade, which is congruent with the morphology of the species. A key to distinguish Salvia gavilanensis from other species of the clade present in the reserve of Tehuacán-Cuicatlán is included.